Analysis of bubble management at different gravity levels by means of an acoustic field. (September 2021) - Huber, Felix; Garcia-Sabaté, Anna; Legendre, Dominique; González-Cinca, Ricard
Highlights: Numerical investigation of bubble trapping by an acoustic wave at levitation positions in different scenarios. Levitation position determined by bubble, liquid and acoustic wave characteristics; bubble initial position; gravity level. Analytical criterion based on balance between average acoustic and buoyancy force to compute levitation position. Bubble management by means of acoustics is of particular interest for space applications. Abstract: Multiphase flows management is a major challenge in many space applications given the different gravity levels involved. While many of the numerical investigations of liquid-gas phenomena deal with the radial bubble behavior and thus the heat exchange, only a few studies have been conducted on the translational motion of bubbles. We present a numerical investigation of the translational motion of gas bubbles immersed in a liquid that is subject to an acoustic wave at different gravity levels. In the computation, the equations for radial oscillation and translational motion are solved simultaneously. The dynamics of bubbles at different gravity levels (from microgravity to hypergravity) are discussed. Bubbles can be trapped by the acoustic wave at levitation positions in different scenarios. The dependence of the levitation position on the initial bubble position at different pressure amplitudes has been computed, giving rise to the bubble being directed to different nodes of the acoustic wave. The bubble radius also determines if and where the bubble levitates. We propose an analytical criterion for the capture of bubbles in a levitation position in terms of a new dimensionless parameter. The criterion is based on the balance between the average acoustic force and the buoyancy force. With the proposed criterion, the position of bubble levitation can be calculated analytically for any scenario.